2007
DOI: 10.1111/j.1439-0507.2007.01412.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory activity of thymol against the formation and viability of Candida albicans hyphae

Abstract: As the capacity of Candida albicans to produce hyphae is considered an important virulence factor in the pathogenesis of candiasis, the aim of this study was to investigate whether thymol, the major component of thyme oil, can interfere with the filamentous forms of Candida albicans and their viability. The morphological transition from yeasts to filamentous forms was investigated by analysing the morphological index (MI), which classifies the differentiated forms and blastoconidia; viability was investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 31 publications
3
36
0
1
Order By: Relevance
“…Therefore, these interactions may cause a greater influx of antifungal agents, resulting in the increase of the inhibition zones and thus reducing the resistances of these yeasts (Table 4) (SANCHEZET et al, 2004;BRAGA et al, 2007;ZORE et al, 2011b).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these interactions may cause a greater influx of antifungal agents, resulting in the increase of the inhibition zones and thus reducing the resistances of these yeasts (Table 4) (SANCHEZET et al, 2004;BRAGA et al, 2007;ZORE et al, 2011b).…”
Section: Discussionmentioning
confidence: 99%
“…Some essential oils have the ability to kill parasites and fungal infections, which is why they are so popular for use in fighting toenail fungus, ringworm and athlete's toenail infection. Another study reported the effectiveness of thymol in eliminating candida fungus [16].…”
Section: Introductionmentioning
confidence: 99%
“…The combination of SYTO-9 and propidium iodide dyes used in he present study uniformly stains tissues in green (live) or red (dead) regardless of cell morphology, since they are based on membrane integrity, being therefore better suited for viability tests in fungal biofilms. Investigating the capacity of thymol to interfere with the hyphal formation of C. albicans and its viability, a study (15) demonstrated that in the absence of thymol, about 93% of fungal cells were found viable, while after 6 h of incubation with 1x MIC, ½ x MIC and ¼ x MIC there were 54%, 29% and 23% damaged cells, respectively. The results of the present study corroborate the aforementioned study when, in absence of antifungal agent, approximately 90% of C. albicans cells were viable; however, the biofilms had their viable mass reduced in the presence of CFM thymol by an even greater proportion, exhibiting 28%, 18% and 31% living cells after 5, 15 and 30 min exposures, respectively (Table 1).…”
Section: Discussionmentioning
confidence: 99%